Role for Tandem Duplication and Lon Protease in AcrAB-TolC- Dependent Multiple Antibiotic Resistance (Mar) in an Escherichia coli Mutant without Mutations in marRAB or acrRAB - Nicoloff, Hervé (American Society for Microbiology, 2006)
A spontaneous mutant (M113) of Escherichia coli AG100 with an unstable multiple antibiotic resistance (Mar) phenotype was isolated in the presence of tetracycline. Two mutations were found: an insertion in the promoter of lon (lon3::IS186) that occurred first and a subsequent large tandem duplication, dupIS186, bearing the genes acrAB and extending from the lon3::IS186 to another IS186 present 149 kb away from lon. The decreased amount of Lon protease increased the amount of MarA by stabilization of the basal quantities of MarA produced, which in turn increased the amount of multidrug effux pump AcrAB-TolC. However, in a mutant carrying only a lon mutation, the overproduced pump mediated little, if any, increased multidrug resistance, indicating that the Lon protease was required for the function of the pump. This requirement was only partial since resistance was mediated when amounts of AcrAB in a lon mutant were further increased by a second mutation. In M113, amplification of acrAB on the duplication led to increased amounts of AcrAB and multidrug resistance. Spontaneous gene duplication represents a new mechanism for mediating multidrug resistance in E. coli through AcrAB-TolC.